Hubungan Efikasi Diri dan Disposisi Matematis Terhadap Kemampuan Penalaran Matematis Peserta Didik Sekolah Dasar - Polem, Rizka Putri Ramadhani; Ziliwu, Enidar; Ziliwu, Ester; Zebua, Syikcan Ayu Hasna; Ndraha, Firsal Yuran Putra; Gea, Berkat Damai; Zebua, Irwan; Mendrofa, Foni Kurniaman; Harefa, Edward (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to evaluate the relationship between mathematical disposition and self-efficacy and mathematical reasoning ability. Quantitative research is used. The non-test research instrument consisted of independent variables, namely self-ability (X1), mathematical disposition (X2), and bound variables, namely mathematical reasoning (Y). This study involved grade IV students of SD MIN 3 Gunungsitoli City for the 2023/2024 school year with a sample of 63 people. The data collection technique uses a questionnaire with a Likert scale and a mathematical reasoning ability test. Data analysis was carried out using multiple linear regression tests. The results showed that self-efficacy influenced mathematical reasoning ability with a path coefficient value of 0.144, mathematical disposition influenced mathematical reasoning ability with a path coefficient value of 0.489, and self-efficacy and mathematical disposition simultaneously affected mathematical reasoning ability of 7.655